2008
DOI: 10.1001/archpsyc.65.7.826
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Glutamatergic Neurotransmission Genes in Alcohol Dependence and Adolescent Risky Drinking Behavior

Abstract: Genetic variations in NR2A have the greatest relevance for human alcohol dependence among the glutamatergic genes selected for their known alteration of alcohol effects in animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 59 publications
9
76
0
Order By: Relevance
“…self-report on the effects of ethanol, subjective high assessment, body sway [180]) showed a systematic distribution difference in 173 genes, including CDH13 and XRCC5 , which had been identified as susceptibility genes for ethanol sensitivity and alcohol dependence elsewhere [161,181,182]. Multiple genes identified in the GSEA were related to glutamatergic signaling, a finding well in line with previous results of animal studies and candidate gene analyses [183,184]. Additionally, the muscarinic receptor (CHRM2) has been replicated in 2 GWAS [185,186] and several other well-replicated candidate genes (i.e.…”
Section: From Genes To Pathwayssupporting
confidence: 61%
“…self-report on the effects of ethanol, subjective high assessment, body sway [180]) showed a systematic distribution difference in 173 genes, including CDH13 and XRCC5 , which had been identified as susceptibility genes for ethanol sensitivity and alcohol dependence elsewhere [161,181,182]. Multiple genes identified in the GSEA were related to glutamatergic signaling, a finding well in line with previous results of animal studies and candidate gene analyses [183,184]. Additionally, the muscarinic receptor (CHRM2) has been replicated in 2 GWAS [185,186] and several other well-replicated candidate genes (i.e.…”
Section: From Genes To Pathwayssupporting
confidence: 61%
“…Previous studies on animal models reported acute liver failure due to increased extracellular concentration of glutamate in the brain [6] which was also correlated with arterial ammonia concentration [9]. Blocking of NMDA receptors through its antagonist MK-801 resulted in delay in the death of rats with acute liver failure supporting the role of NMDA receptors in this disease [24].…”
Section: Discussionmentioning
confidence: 75%
“…A variable GTn repeat in the 5'-regulatory region of N-methyl-Daspartate GRIN2A subtype was identified and significantly associated with alcohol dependence [14,23]. A study also showed GRIN2A gene to be of the highest relevance in alcohol dependence among ten glutamate pathway genes studied [24]. Recently, a study found SNPs of NMDA receptors' effect on neural activity of the brain related to alcohol cues and craving [25].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent evidence supports genetic associations with alcoholism of the glutamate receptor ionotropic N-methyl D-aspartate 2A (GRIN2A) gene [57] and MAOA genes [27]. In future work, the contributions of the GRIN2A and MAOA genes to personality traits in alcohol dependence should be further tested.…”
Section: Alcoholismmentioning
confidence: 97%